Geometry of the form and designs of Ilkhani tombs' tower of Azerbaijan (Case study: Qarabagh Bardaeh tomb' tower) - Tavakkoli, Behrouz; Cinmarasl, Raana (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The seventh and eighth centuries of the Hijri calender were the era when Azerbaijan's architecture flourished. During this period, a special style of funerary architecture was developed in the form of a tower-shaped tomb, the scope of its effects extending from Azerbaijan and reaching Khorasan and Turkestan in the east, and Asia Minor and Mamluk Egypt. Considering the centrality of Azerbaijan during the period of the Ilkhanite of this region, the architectural styles flourished in this temporal and spatial period, which later became known as Azeri-style architecture. Parallel to other religious monuments, the tower-shaped tombs found a privileged position in Islamic architecture. Its best examples are the mausoleum tower of Bardaeh in Qarabagh, Sheikh Safi, and Sheikh Heydar, Soltanieh, Ghaffarieh and Qara Baghlar. The purpose of the present study is to recognize the architectural and decorative structure, and to analyze the geometric patterns used in the Azerbaijan tombs, with emphasis on the Qarabagh Bardaeh tomb tower, as a persistent pattern. In order to achieve these goals, the tombs were studied with an interpretive and qualitative strategy, through historical and library studies and field analysis. The designs and decorations were documented, recognized and analyzed.